Sovereign Risk and Asset and Liability Management : Conceptual Issues - Das, Udaibir (IMF Working Papers; Working Paper ;, 2012)
Country practices towards managing financial risks on a sovereign balance sheet continue to evolve. Each crisis period, and its legacy on sovereign balance sheets, reaffirms the need for strengthening financial risk management. This paper discusses some salient features embedded in in the current generation of sovereign asset and liability management (SALM) approaches, including objectives, definitions of relevant assets and liabilities, and methodologies used in obtaining optimal SALM outcomes. These elements are used in developing an analytical SALM framework which could become an operational instrument in formulating asset management and debtor liability management strategies at the sovereign level. From a portfolio perspective, the SALM approach could help detect direct and derived sovereign risk exposures. It allows analyzing the financial characteristics of the balance sheet, identifying sources of costs and risks, and quantifying the correlations among these sources of risk. The paper also outlines institutional requirements in implementing an SALM framework and seeks to lay the ground for further policy and analytical work on this topic.